Accelerated step-up regimes for feedlot heifers following oral dosing with Lactipro (Megasphaera elsdenii strain NCIMB 41125) - Miller, K.; Van Bibber, C.L.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Cattle entering feedlots typically are adapted to finishing diets over a period of 2 to 4 weeks by gradually replacing forages with concentrate feeds using a series of step-up diets. Without proper adaptation, naïve cattle are highly susceptible to ruminal acidosis, a disorder associated with excessive production and accumulation of organic acids within the rumen. One of the key metabolic intermediates associated with the manifestation of acidosis is lactic acid, which is derived from fermentation of readily available starches and sugars. Streptococcus bovis is a prolific, rapidly growing, and opportunistic organism that thrives in the presence of readily fermented starches and sugars, and is an important inhabitant of the rumen that is recognized for its ability to produce large quantities of lactate. In unadapted cattle, the relative absence of lactate-utilizing bacteria can lead to the accumulation of lactate, thus predisposing the animals to acidosis. In traditional step-up programs, the gradual replacement of roughages with concentrate feeds provides ample time for proliferation of lactate-utilizing species of bacteria, the most important of which is Megasphaera elsdenii. Lactipro (MS Biotech, Inc., Wamego, KS) is a novel class of probiotic consisting of a highly prolific strain of Megasphaera elsdenii. Because Megasphaera elsdenii is an obligate anaerobe, it must be administered orally to avoid exposure to oxygen. In previous experiments with Lactipro, we have observed that a single oral dose results in rapid colonization of Megasphaera elsdenii within the rumen, effectively preventing the accumulation of lactate following an abrupt diet change from forage to concentrate. The present study was designed to evaluate different step-up regimens, with the objective of decreasing the time and number of diets required to place cattle on high-concentrate finishing diets.
Keywords: Beef; Feedlot heifers; Lactipro; Performance; Megasphaera elsdenii